2012
DOI: 10.1002/alr.21069
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory outcomes following endoscopic pituitary surgery with or without septal flap reconstruction: a randomized controlled trial

Abstract: Endoscopic pituitary surgery results in decreased olfaction with or without deploying a septal flap. However, use of the HB flap for reconstruction can worsen hyposmia at least 6 months after surgery. Olfaction should be considered when use of the HB flap is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 13 publications
0
92
1
2
Order By: Relevance
“…Of the studies focusing on objective olfactory outcomes after ESBS in the sella/parasella (Table ), only three found differences in postoperative olfaction after ESBS . Reasons for the discrepancy observed in those three studies could be differences in technique or biases in pre‐ and postoperative patient counseling, the latter of which may affect patient self‐confidence when taking the olfaction test.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies focusing on objective olfactory outcomes after ESBS in the sella/parasella (Table ), only three found differences in postoperative olfaction after ESBS . Reasons for the discrepancy observed in those three studies could be differences in technique or biases in pre‐ and postoperative patient counseling, the latter of which may affect patient self‐confidence when taking the olfaction test.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the increased number of EETSA procedures, studies concerning the quality of life of patients after EETSA have recently been reported . In our previous studies, olfactory changes increased significantly after EETSA .…”
Section: Introductionmentioning
confidence: 88%
“…However, the flap described by Tam et al has little respect for the olfactory strip on the septum. 8 In contrast, the technique described in this study utilizes the nasal floor for width. Such mucosa is thick and makes for good reconstruction.…”
Section: Discussionmentioning
confidence: 97%
“…3,8,9 Unfortunately, standardization of surgical technique does not exist and what is described surgically in some series is not the same as others. In particular, the degree of tissue resection and the location of the nasoseptal flap differ greatly between centers with fellowship-trained rhinologists and those without.…”
Section: Introductionmentioning
confidence: 99%